Hemoglobin A1C Percentage in Nonhuman Primates: A Useful Tool to Monitor Diabetes before and after Porcine Pancreatic Islet Xenotransplantation - Marco Marigliano; Anna Casu; Suzanne Bertera; Massimo Trucco; Rita Bottino (Journal of Transplantation)
Non-human primates (NHPs) are a very valuable experimental model for diabetes research studies including experimental pancreatic islet transplantation. In particular NHPs are the recipients of choice to validate pigs as possible source of pancreatic islets. The aim of this study was to quantify glycated hemoglobin percentage in NHPs and to assess whether changes in values reflect the metabolic trends after diabetes induction and islet transplantation. Sera from 15 NHPs were analyzed. 9 NHPs were rendered diabetic with streptozotocin (STZ), and 3 of them received porcine islet transplants. Hemoglobin A1c (HbA1c) percentage was measured with an assay based on a latex immunoagglutination inhibition methodology. Whereas diabetes and its duration were associated with increasing HbA1c levels, postislet transplantation blood glucose normalization was paralleled by a decrease in the HbA1c percentage. Our data provide evidence that HbA1c is a useful tool to monitor glucose metabolism in NHPs.